2005
DOI: 10.3354/meps299277
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of coral reef fishes along a coral reef-seagrass gradient: edge effects and habitat segregation

Abstract: Coral reefs and seagrass beds are often located adjacent to one another, but little is known about the degree to which their fish communities are interlinked. To determine whether coral reef fishes on the coral reef are interlinked with or segregated from fishes on adjacent seagrass beds, a 60 m coral reef -seagrass gradient was studied on the island of Zanzibar in the western Indian Ocean. Using underwater visual census, coral reef fishes were surveyed in 4 habitat zones: (1) a coral patch reef, (2) seagrass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 29 publications
5
62
0
Order By: Relevance
“…Vanderklift et al (2007) examined fish communities at varying distances (0 to 1100 m) from rocky reefs in Western Australia and observed an abrupt decline of small predatory fish within the first 30 m from the reef, indicative of a negative edge effect. Similarly, Dorenbosch et al (2005) in the western Indian Ocean observed an edge effect for coral reef-associated species and generalist species, where fish densities and species richness decreased significantly within 30 m of the patch reef boundary.…”
Section: Edge Effectsmentioning
confidence: 99%
“…Vanderklift et al (2007) examined fish communities at varying distances (0 to 1100 m) from rocky reefs in Western Australia and observed an abrupt decline of small predatory fish within the first 30 m from the reef, indicative of a negative edge effect. Similarly, Dorenbosch et al (2005) in the western Indian Ocean observed an edge effect for coral reef-associated species and generalist species, where fish densities and species richness decreased significantly within 30 m of the patch reef boundary.…”
Section: Edge Effectsmentioning
confidence: 99%
“…In 15 of these sites, the coexistence of corals and seagrass was found suggesting a significant rate of biodiversity in the study area. The analysis along four transects from the coast indicated that seagrass beds were always closer to the land and reached more extension in case of more gentle bottom slopes as also observed in other tropical islands [43][44][45].…”
Section: Resultsmentioning
confidence: 95%
“…Furthermore, habitat heterogeneity (e.g. configuration, accessibility) and the co-occurrence of different structured habitats in the seascape play important roles in habitat selection and fish distribution patterns (Dorenbosch et al 2005, Nakamura et al 2007, Nagelkerken 2009). Nakamura et al (2007) showed that pelagic larvae preferred heterogeneous seagrass beds and settled on patch reefs within seagrass beds, rather than on monotonous seagrass fields or on sand patches.…”
Section: Discussionmentioning
confidence: 99%